2022
DOI: 10.1186/s12916-022-02520-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predispositions to psychiatric disorders and the risk of COVID-19

Abstract: Background Whether a genetic predisposition to psychiatric disorders is associated with coronavirus disease 2019 (COVID-19) is unknown. Methods Our analytic sample consisted of 287,123 white British participants in UK Biobank who were alive on 31 January 2020. We performed a genome-wide association study (GWAS) analysis for each psychiatric disorder (substance misuse, depression, anxiety, psychotic disorder, and stress-related disorders) in a rando… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…(6, 7) Some studies have reported common alterations in biological pathways for psychiatric disorders and COVID-19, (8) which suggests a potential role for shared common genetic risk factors between both conditions. In line with these observations, a genetic predisposition to psychiatric disorders has been associated with COVID-19 susceptibility and severity, (9) and recent studies have reported signi cant genetic correlations between depression and COVID-19. (10) Despite shared genetic overlap, studies using genetic data have failed to nd evidence of causal associations between selected psychiatric disorders and COVID-19 in support of the results obtained in observational studies.…”
Section: Introductionmentioning
confidence: 58%
“…(6, 7) Some studies have reported common alterations in biological pathways for psychiatric disorders and COVID-19, (8) which suggests a potential role for shared common genetic risk factors between both conditions. In line with these observations, a genetic predisposition to psychiatric disorders has been associated with COVID-19 susceptibility and severity, (9) and recent studies have reported signi cant genetic correlations between depression and COVID-19. (10) Despite shared genetic overlap, studies using genetic data have failed to nd evidence of causal associations between selected psychiatric disorders and COVID-19 in support of the results obtained in observational studies.…”
Section: Introductionmentioning
confidence: 58%
“…Alternatively, individuals who had taken a COVID-19 test might also have temporarily reduced social contact, i.e., being quarantined or isolated, to avoid infecting others, resulting in negative impact on mental health [38]. On the other hand, studies conducted by our [39,40] and other research groups [41] demonstrated a bidirectional association between COVID-19 and psychiatric disorders, suggesting that individuals with propensity for psychiatric disorders may be more vulnerable for COVID-19 infection and adverse outcomes. With respect to the test result, we observed a similar increased risk of anxiety and depression for individuals with both negative and positive results, which is in agreement with Abel et al's finding [12].…”
Section: Discussionmentioning
confidence: 97%
“…created a latent general addiction risk factor and found that the PGS based on this factor were associated with substance use disorders, psychopathologies, somatic conditions, and environments associated with the onset of addictions. In another study, a PGS based on substance misuse was significantly predictive of COVID-19 [80].…”
Section: Polygenic Prediction Of Substance Use Disordersmentioning
confidence: 94%